2016
DOI: 10.1186/s10152-016-0479-2
|View full text |Cite
|
Sign up to set email alerts
|

Synchronism of naupliar development of Sacculina carcini Thompson, 1836 (Pancrustacea, Rhizocephala) revealed by precise monitoring

Abstract: Sacculina carcini is member of a highly-specialized group of parasitic cirripeds (Rhizocephala) that use crabs (Carcinus maenas) as hosts to carry out the reproductive phase of their life cycle. We describe the naupliar development of S. carcini Thompson, 1836 from a very precise monitoring of three different broods from three specimens. Nauplii were sampled every 4 h, from the release of the larvae until the cypris stage. Larval development, from naupliar instar 1 to the cypris stage, lasts 108 h at 18 °C. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…As a result, the genera Peltogasterella [4,57], Peltogaster [2], Sacculina [5], Polyascus [6], and Heterosaccus [54] were found to have five naupliar stages. Careful monitoring and observation of larvae every 4 h showed that the pelagic period of the wellstudied species Sacculina carcini also includes five naupliar stages [58], but not four stages, as suggested previously [10,61]. However, only four naupliar stages were found in Parasacculina sinensis [9] and Polyascus planus [59], despite that the larvae of the latter species were observed every 6 h.…”
Section: The Number Of Naupliar Stages and Durationmentioning
confidence: 83%
See 3 more Smart Citations
“…As a result, the genera Peltogasterella [4,57], Peltogaster [2], Sacculina [5], Polyascus [6], and Heterosaccus [54] were found to have five naupliar stages. Careful monitoring and observation of larvae every 4 h showed that the pelagic period of the wellstudied species Sacculina carcini also includes five naupliar stages [58], but not four stages, as suggested previously [10,61]. However, only four naupliar stages were found in Parasacculina sinensis [9] and Polyascus planus [59], despite that the larvae of the latter species were observed every 6 h.…”
Section: The Number Of Naupliar Stages and Durationmentioning
confidence: 83%
“…It was suggested that this is the sixth rudimentary seta [57]. In Sacculina carcini, such a spine was not found in all examined specimens; therefore, the authors believe that it cannot be considered a true rudimentary seta [58]. In Lernaeodiscus rybakovi, S. carcini, and Heterosaccus papillosus, the fifth antennular seta is located on the middle segment at the early stages; later it is shifted to the distal segment [54,58].…”
Section: Appendagesmentioning
confidence: 96%
See 2 more Smart Citations
“…All rhizocephalans infect other crustaceans (Høeg, 1995;Høeg and Lützen, 1995). Their unique life cycle begins with the hatching of sexually dimorphic nauplii, which upon several molts, metamorphose into male and female cyprids (Trédez et al, 2017). Female cyprids would develop into kentrogon larvae and infect hosts by penetrating hosts' integument, thereby transferring parasitic material (vermigon) into the hemolymph (Glenner and Høeg, 1994;Glenner, 2001).…”
Section: Introductionmentioning
confidence: 99%